2017
DOI: 10.47992/ijhsp.2581.6411.0009
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Foramen Magnum in Adult Dry Skulls in Dakshina Kannada

Abstract: The objectives of the present study were to determine the type and morphometric measurements of Foramen magnum (FM) in dry human skulls of Dakshina Kannada district of Southern India. Material and Methods: The present study included 50 adult human skulls of which 32 were males and 18 females. The type of foramen magnum observed macroscopically. Antero-posterior (APD) and transverse diameters (TD) were measured by using stainless steel electronic digital callipers. Foramen magnum Index (FMI) was calculated by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…In the present study, tetragonal shape of foramen magnum was in 1.73% cases (06 out of 347 skulls).The finding of the present study is lower than the findings of Radhika PM et al [27](2014)in 6%, Bhaskar R et al [11](2017) in 30%, Veeramani R et al [15] 1 & 2) These higher percentages may be due to racial differences as the population in the above studies differs from population of the present study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, tetragonal shape of foramen magnum was in 1.73% cases (06 out of 347 skulls).The finding of the present study is lower than the findings of Radhika PM et al [27](2014)in 6%, Bhaskar R et al [11](2017) in 30%, Veeramani R et al [15] 1 & 2) These higher percentages may be due to racial differences as the population in the above studies differs from population of the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…In the present study, round shape foramen magnum was found in 30.84% cases (107 out of 347 skulls). The value of this study was almost similar to the values of studies done by Riyaz ZH et al [13](2015) in 29.50% and Chandekar KS et al [24](2017) in 30.43 % cases; lower than the findings of Muthukumar N et al [25](2005) in 54% and Ajay R et al [26] (2015) in 35% cases; higher than the findings of Chethan P et al [5](2012) in 22.6%, Radhika PM et al [27] (2014) in 20%, Ganapathy A et al [28](2014) in 9%, Gopalkrishana K et al [29] (2015) in 25%, Saini K [8](2015) in 19%, Bhaskar R et al [11] (2017) in 16%, Veeramani R et al [15] (2018) in 15%, Aragão JA et al [19](2014) in 15.5%, Kumar A et al [16](2015) in 20%, Pires LA et al [17] (2016) in 24.67%, Revankar S et al [21] in 17.5%, Sharma DK et al [22] in 14.67% and Sharma A et al [23] in 3.9% cases. (Table1 & 2) This difference may be due to population variation.…”
Section: Discussionmentioning
confidence: 85%